1991
DOI: 10.1159/000147081
|View full text |Cite
|
Sign up to set email alerts
|

Architectural and Fiber Type Distribution Properties of Selected Rhesus Leg Muscles: Feasibility of Multiple Independent Biopsies

Abstract: In experiments involving primates, e.g. before and after spaceflight, needle biopsies were thought to be a logical and feasible means of obtaining metabolic and morphological information from skeletal muscles. However, the feasibility of obtaining consistent, repeatable biopsies from individual muscles had to be demonstrated prior to the acceptance of this procedure. To study this approach, the architectural properties and the fiber type distributions at three levels and two regions along the proximodistal axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In agreement with histoenzymatic studies in nonhuman primates [15,18,19,42,43) and other mammals [44|, we found significant variations between the superficial and deep parts of the various muscles, with the exception of the relatively homo geneous soleus. Maximum heterogeneity of fibre percentages was found in triceps medialis (newborn as well as adult).…”
Section: Resultssupporting
confidence: 91%
“…In agreement with histoenzymatic studies in nonhuman primates [15,18,19,42,43) and other mammals [44|, we found significant variations between the superficial and deep parts of the various muscles, with the exception of the relatively homo geneous soleus. Maximum heterogeneity of fibre percentages was found in triceps medialis (newborn as well as adult).…”
Section: Resultssupporting
confidence: 91%
“…Each muscle was sampled at one location, and this biopsy was considered representative of the entire muscle, thereby assuming that regional variation within a muscle is smaller than variation between muscles. This assumption is supported by past work in rhesus monkeys, where fiber-type percentage variability between subjects was demonstrated to be much greater than between biopsies within a muscle in a single subject (Roy et al, 1991), and in human paraspinal muscles, where fiber-type distribution was independent of biopsy depth (Regev et al, 2010).…”
Section: Limitationsmentioning
confidence: 54%
“…Another similarity between the Rhesus and other mammals was the differential recruitment of slow versus fast muscles with respect to speed of locomotion. For example, the MG muscle, composed of a high proportion of fast, fatigable motor units (Roy et al 1991a), was more heavily recruited at the faster than the slower speeds of locomotion, whereas the predominantly slow Sol muscle was already heavily recruited at the slower treadmill speeds (Figs. 7 and 8).…”
Section: Speed-related Changes In Gait Parameters and Muscle Activitymentioning
confidence: 99%